Impact of Iron Deficiency on the Growth and Bioelectrical Profile of Different Gut Bacteria - Elisa Quarta; Marwane Bourqqia‐Ramzi; David Muñoz‐Rodriguez; María Teresa García‐Esteban; Antonio Murciano‐Cespedosa; Álvaro Mateos González; Francisco José Conejero‐Meca; Juan Lombardo‐Hernandez; Jesús Mansilla‐Guardiola; Simona Baroni; Simonetta Geninatti Crich; Stefano Geuna; et al. (MicrobiologyOpen)
ABSTRACT Scope: Iron deficiency (ID) is the most common nutritional deficiency worldwide, impacting gut bacteria's metabolism and cellular biochemistry, but its effects on the microbiota‐gut‐brain axis (MGB) are poorly understood. Early‐life ID‐related dysbiosis is linked to neurodevelopmental impairments like autism and attention deficit hyperactivity disorder. Studying ID's impact on bacterial signaling can guide interventions to target MGB in iron‐deficient populations. This study examined the responses of Escherichia coli (E. coli) and Limosilactobacillus reuteri (L. reuteri) to in‐vitro ID conditions using the iron chelator 2,2’‐Bipyridyl (BP). Methods and Results: We assessed and modeled their growth and cultivability and explored their bioelectric profiles using the voltage‐sensitive dye DiBAC4(3). Results showed differential responses: L. reuteri's growth and cultivability were unaffected by BP, while E. coli's growth rate and cultivability decreased under ID. Additionally, we created a deterministic mathematical model that demonstrated a decrease in the population's average reproduction rate in E. coli under ID. Only E. coli exhibited an altered bioelectric profile, marked by increased cell depolarization in ID conditions, which was largely rescued upon the addition of a saturating concentration of iron. Conclusion: These findings highlight specific bioelectrical responses in gut bacteria to ID. Understanding this variability is crucial for deciphering the microbiota's role in health and disease, particularly concerning nutritional iron imbalance and bacterial signaling in the MGB.